Investigation of chromosome aneuploidies in early porcine embryos using comparative genomic hybridization - Hornak, M; Hulinska, P; Musilova, P; Kubickova, S; Rubes, J (Cytogenetic and genome research, 2009)
Although numerical chromosome errors are known to be prevalent in early human embryos and are likely to be a considerable factor influencing the mortality of early embryos and implantation failure, in domestic animals data about the frequency and nature of errors is limited. The objectives of this study were to investigate the whole chromosome set of in vivo obtained early pig embryos, applying methods of whole genome amplification and comparative genomic hybridization (CGH) and to contribute to the comprehensive understanding of the topic. The embryos were collected from gilts 72 h after insemination. Further, they were lysed and underwent whole genome amplification by multiple displacement amplification. In a subsequent CGH, amplified DNA was compared to control DNA using different fluorescent labeling and hybridization to male pig mitoses. 11 (14.3%) of the 77 pig embryos examined were observed to be aneuploid. We found chromosome errors comprising loss/gain of one or a few chromosomes (10.4%) but also extensive chromosome imbalances (3.9%). Chromosomes 8, 11, 12, 13, 17, and X were most frequently involved in aneuploidies, when compared to chromosomes 2, 9, and 18, which were rarely involved in chromosome errors.
Keywords: prasata; Swine; polymerázová řetězová reakce; Male; hybridizace in situ fluorescenční; chromozomální aberace; mužské pohlaví; Genomics; hybridizace nukleových kyselin; Chromosome Aberrations; aneuploidie; Animals; ženské pohlaví; Aneuploidy; zvířata; In Situ Hybridization, Fluorescence; Polymerase Chain Reaction; Female; Nucleic Acid Hybridization; genomika